KAJIAN PENANGANAN BANJIR SUNGAI BERINGIN SEMARANG DENGAN MENGGUNAKAN SISTEM LONG STORAGE - Muhammad Ficky Meilaci Wibowo; Randy Arnatha; Suharyanto Suharyanto; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
One of the phenomenon of the river is flood, which is caused by the inability of the river to accommodate the rain before it is streamed to the sea. Study location in Beringin River area Wonosari Semarang City is being one of the areas that is often experienced this. The negative impacts such as inhibiting people activities, infrastructure damage, and paralysis of economic activity, making this can’t be ignored. So, needed a handling effort to minimize or even prevent flooding. In this final task, the flood control system that used is the long storage which it is an extend reservoir on Beringin river area, Semarang. The planning process of long storage begins with primary and secondary data collection, and got 1993-2012 (20 years) rain data from 3 (three) different rain stations which is Tugu station, Mijen station, and Mangkangwaduk station with total of Beringin River area is 26,58 km2. Hydrological analysis which includes determining rainfall average using Thiessen method, frequency analysis with probability distribution, data testing using Chi-Kuadrat and Smirnov-Kolmogorof, Intensity of the rain plan calculating using Mononobe and ABM (Alternating Block Methode, and determining flood discharge plan using HSS Gama I. And then hydraulic analysis with flood routing and backwater to determining the needed of long storage capacity to plan the design of water building and the components. The last is budget planning and job scheduling of long storage. From hydrological analysis obtained with the maximum flood debit for a period of 25 years m3/sec 216,897. Obtained from that debit of flood water level +8,62. For the design of water building, including lighthouse weir (spillway) 22 meters width, 3 units of drain floodgates each 1,5 meters width, levees (retaining wall) 2 kilometers length, and bridge services. Implementation is planned in 6 months at a cost of Rp 17.316.641.000,00.-. From this Long Storage planning, it is expected to cope flood that occurred in Beringin River area, Semarang.